Perbaikan Performan dan Reproduksi Sapi melalui Rehabilitasi Padang Rumput dan Pemanfaatan Jerami Peram oleh Kelompok Tani - Khalil Khalil; Dwi Ananta; Andri Andri; Yulia Yelita (Institut Pertanian Bogor, 2026)
This community service program aimed to strengthen a farmer group's capacity to manage communal pasture and to utilize preserved rice straw as an alternative feed to improve cattle production and reproductive performance. The scope of activities included participatory assistance in pasture rehabilitation and hands-on training on the preparation and application of preserved rice straw. A participatory approach was applied through training sessions, field practice, and continuous mentoring involving all group members. The program activities comprised pasture rehabilitation through land preparation, weed control, and the replanting of forage grasses and leguminous species, as well as the adoption of preserved rice straw in daily feeding practices. The program's impacts were evaluated collaboratively through observations and records on participants’ satisfaction and program mastery, pasture conditions, and cattle performance before and after implementation. The results showed improved pasture management, reflected by reduced weed dominance and increased forage availability, as well as better feed continuity during the dry season. The application of preserved rice straw improved body condition, weight gain, and reproductive indicators in cattle. In conclusion, the community service effectively enhanced the farmer group's capacity for pasture rehabilitation, combined with preserved rice straw feeding, resulting in better cattle growth and reproductive performance.